Implementation of the Principles of Necessity and Proportionality in the Sharing of Customer Data by Banks with Vendors - Prasanti, Nandani Bayu; Gunadi, Ariawan (Universitas Islam Sultan Agung, 2025)
In the era of digital transformation in the banking sector, there has been an increasing practice of sharing customer data with third parties, such as service providers or vendors. This practice poses legal challenges, particularly concerning the fulfillment of the principles of necessity and proportionality in the protection of personal data. This study aims to analyze the implementation of these two principles in the collaborative practices between banks and vendors regarding the protection of customers’ personal data. This normative juridical research employs a conceptual and statutory approach, using legal materials obtained from national and international regulations, academic journals, and best practices in the banking sector. The findings indicate the need for clear and comprehensive internal bank policies on personal data protection in third-party data processing, serving as a guideline to ensure compliance with personal data protection principles.